S'more murders [large type] - Corrigan, Maya (Corrigan, Maya. Five-ingredient mystery., 2018)
Since catering themed events is a good way to make extra cash, Val agrees to board the Titanic--or at least cater a re-creation of the doomed journey on a yacht. The owner of the yacht, who collects memorabilia related to the disaster, wants Val to serve the last meal the Titanic passengers ate . . . while his guests play a murder-mystery game. But it is the final feast for one passenger who disappears from the ship. And that's only the tip of the iceberg.